(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The objective of this study was to develop a novel self-nanoemulsifying drug delivery system which produced very small and uniform emulsion droplets, resulting in enhanced solubility, dissolution, and oral bioavailability of poorly water-soluble rosuvastatin calcium. Material and Methods: The effects of oil, surfactant, and cosurfactant on the drug solubility were assessed, and pseudoternary phase diagrams were plotted. Among the liquid SNEDDS formulations tested, the liquid SNEDDS composed of cinnamon oil (oil), Cremophor RH 40 (surfactant), and Transcutol P (cosurfactant) at a ratio of 1:5 (o/Smix), produced the smallest emulsion droplet size. The rosuvastatin-loaded liquid SNEDDS formulation was assessed for the emulsion droplet size, solubility, and dissolution of the emulsified SNEDDS and compared to the pure drug. Different SNEDDS formulations of rosuvastatin calcium were prepared by aqueous phase titration method. Prepared SNEDDS was filled in capsule shells as drugs with high solubility or low dose can be filled in capsule shell. Prepared SNEDDS was subjected to different thermodynamic stability tests. Thermodynamically stable SNEDDS was selected for self-nanoemulsification efficiency test. Selected formulations were characterized in terms of droplet size distribution, viscosity. Finally, selected SNEDDS (F1–F8) was subjected to in vitro dissolution/drug release studies. Results and Discussion: Droplet size and viscosity of formulation F6 were found to be lowest as compared to other formulations. The results of zeta potential indicated the formation of stable SNEDDS. In vitro drug release studies showed 97.7% release of drug from optimized formulation F6, where initial drug release profile of rosuvastatin calcium from optimized formulation F6 was found to be much faster than marketed rosuvastatin calcium capsule. Conclusion: Thus, this novel SNEDDS developed represents a potentially powerful oral delivery system for rosuvastatin calcium to enhance solubility and thereby bioavailability.